AMP Kinase Promotes Bcl6 Expression in both Mouse and Human T cells - Xie, Markus M. (Mol Immunol, 2016)
The transcription factor Bcl6 is a master regulator of follicular helper T (T(FH)) cells, and understanding the signaling pathway that induces Bcl6 and T(FH) cell differentiation is therefore critical. IL-2 produced during T cell activation inhibits Bcl6 expression but how T(FH) cells evade IL-2 inhibition is not completely understood. Here we show that Bcl6 is highly up-regulated in activated CD4 T cells following glucose deprivation (GD), and this pathway is insensitive to inhibition by IL-2. Similar to GD, the glucose analog 2-deoxyglucose (2DG) inhibits glycolysis, and 2DG induced Bcl6 expression in activated CD4 T cells. The metabolic sensor AMP kinase (AMPK) is activated when glycolysis is decreased, and the induction of Bcl6 by GD was inhibited by the AMPK antagonist compound C. Additionally, activation of AMPK by the drug AICAR caused Bcl6 up-regulation in activated CD4 T cells. When mice were immunized with KLH using AICAR as an adjuvant, there was a strong T(FH)–dependent enhancement of KLH-specific antibody (Ab) responses, and higher Bcl6 expression in T(FH) cells in vivo. Activation of AMPK strongly induced BCL6 and the up-regulation of T(FH) cell marker expression by human CD4 T cells. Our data reveal a major new pathway for T(FH) cell differentiation, conserved by both mouse and human T cells. Mature T(FH) cells are reported to have a lower metabolic state compared to T(H)1 cells. Our data indicates that decreased metabolism may be deterministic for T(FH) cell differentiation, and not simply a result of T(FH) cell differentiation.